1987
DOI: 10.1159/000153679
|View full text |Cite
|
Sign up to set email alerts
|

Gc and Tf Subtypes in Greece

Abstract: PAGIF was used to investigate the distribution of Gc and Tf subtypes in a Greek population sample. The gene frequencies were compared to those reported for other European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The Thessa loniki gene frequencies resemble those from other populations in Europe, and in deed fall clearly amongst the European cluster distinguished by Papiha et al [1982], Though there is a slight suggestion that the G clF frequencies may be a little higher than in northern Europe and GclS a little lower, certainly the results do not confirm the significant differences from other European populations reported by Kouvatsi and Triantaphyllidis [1987], and indeed the phenotype frequencies that they observed differ significantly (x2 = 23.6, d.f. 5, p< 0.001) from those of the present series.…”
Section: Resultsmentioning
confidence: 59%
“…The Thessa loniki gene frequencies resemble those from other populations in Europe, and in deed fall clearly amongst the European cluster distinguished by Papiha et al [1982], Though there is a slight suggestion that the G clF frequencies may be a little higher than in northern Europe and GclS a little lower, certainly the results do not confirm the significant differences from other European populations reported by Kouvatsi and Triantaphyllidis [1987], and indeed the phenotype frequencies that they observed differ significantly (x2 = 23.6, d.f. 5, p< 0.001) from those of the present series.…”
Section: Resultsmentioning
confidence: 59%
“…The highest fre quency of the D variant is now found among the Mongols, in China; the fre quency of B and D variants was 2.9% in Mongols and 8.2% in Zhuang [Du Ruo-fu and Chen Liang-zhong, 1986]. The D vari ants found in this study were most likely DC hi-In Caucasoid populations the fre quency of rare variants is mostly between 2 and 4% [Walter et al, 1983;Lai et al, 1986;Kouvatsi and Triantaphyllidis, 1987]. This is in agreement with our data for Russians (2%).…”
Section: Resultsmentioning
confidence: 67%
“…1983;Giari et al. 1985;Kouvatsi and Triantaphyllidis, 1987;Kamboh and Fer rell, 1987], The C6 allele previously found in North Africans from Algeria and spo radically in Caucasians [Kühnl et al, 1981;Pascali and Auconi, 1983;Weidinger et al, 1984;Carracedo and Con cheiro, 1983] was observed in 2 individu als.…”
Section: Resultsmentioning
confidence: 95%